MiR- 211 represses apoptosis of nerve cells in rats with cerebral infarction through PI3K/AKT signaling pathway: MiR-211 in rats with cerebral infarction - Li, Fang; Liu, Hongxin (Cellular and Molecular Biology, 2023)
To investigate the effect of micro ribonucleic acid (miR)-211 on the apoptosis of nerve cells in rats with cerebral infarction through phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. A total of 36 Sprague-Dawley (SD) rats were randomly divided into sham operation group (n=12), model group (n=12) and miR-211 mimics group (n=12). Only the common carotid artery, external carotid artery, and internal carotid artery were exposed in sham operation group, and the models of cerebral infarction were constructed via suture method in the other two groups. After modeling, the rats in sham operation group and model group were intraperitoneally injected with normal saline, while those in miR-211 mimics group were given miR-211 mimics via intraperitoneal injection. At 2 weeks after intervention, samples were collected. Neurological deficit in rats was assessed using the Zea-longa score, and Nissl staining assay was performed to observe neuronal morphology. Western blotting (WB), quantitative polymerase chain reaction (qPCR) assay and enzyme-linked immunosorbent assay (ELISA) were employed to measure the relative protein expressions of PI3K and phosphorylated AKT (p-AKT), mRNA expression of miR-211 and content of B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X protein (Bax), respectively. Additionally, the apoptosis was detected via terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) assay. The neuronal morphology was normal in sham operation group, while it was disordered in model group, with damaged neurons. In miR-211 mimics group, the morphology of neurons was improved. The Zea-longa score was obviously higher in model group and miR-211 mimics group than that in sham operation group (P<0.05), while it was notably lower in miR-211 mimics group than that in model group (P<0.05). Compared with those in sham operation group, the relative protein expression levels of PI3K and p-AKT remarkably declined in model group and miR-211 mimics group (P<0.05), whereas they were clearly higher in miR-211 mimics group than those in model group (P<0.05). The relative expression level of miR-211 was lower in model group and miR-211 mimics group than that in sham operation group (P<0.05), while it was markedly higher in miR-211 mimics group than that in model group (P<0.05). In comparison with sham operation group, model group and miR-211 mimics group had remarkably increased content of Bax and evidently lowered content of Bcl-2 (P<0.05), whereas compared with model group, miR-211 mimics group displayed clearly reduced Bax content and notably raised Bcl-2 content (P<0.05). The apoptosis rate was distinctly higher in model group and miR-211 mimics group than that in sham operation group (P<0.05), while it was visibly lower in miR-211 mimics group than that in model group (P<0.05). MiR-211 represses the apoptosis of nerve cells in rats with cerebral infarction by up-regulating the PI3K/AKT signaling pathway, thereby protecting nerves.